2004
DOI: 10.1002/chin.200434192
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Cleavage of the Se—Se Bond in the Presence of a Zn/AlCl3 System: Synthesis of Selenol Esters.

Abstract: Organo-selenium compounds Organo-selenium compounds S 0130Reductive Cleavage of the Se-Se Bond in the Presence of a Zn/AlCl 3 System: Synthesis of Selenol Esters. -(MOVASSAGH*, B.; SHAMSIPOOR, M.; JOSHAGHANI, M.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It was found that the substitution of Cys by Sec is very conserved, and only minor structural distortion and biological activity variations happened in all cases [26][27][28][29]. Therefore, due to the importance of disulfide bridges for protein structures and activity, the study of the reductive cleavage of diselenide (Se-Se) bonds has started to attract attention [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the substitution of Cys by Sec is very conserved, and only minor structural distortion and biological activity variations happened in all cases [26][27][28][29]. Therefore, due to the importance of disulfide bridges for protein structures and activity, the study of the reductive cleavage of diselenide (Se-Se) bonds has started to attract attention [30,31].…”
Section: Introductionmentioning
confidence: 99%